Combined use of adipose derived stem cells and TGF-β3 microspheres promotes articular cartilage regeneration in vivo. (3rd April 2018) - Sun, Q; Zhang, L; Xu, T; Ying, J; Xia, B; Jing, H; Tong, P
Abstract: We investigated enhancement of articular cartilage regeneration using a combination of human adipose derived stem cells (hADSCs) and TGF-β3 microspheres (MS) in vivo. Poly-lactic-co-glycolic acid (PLGA)MS were prepared using a solid/oil/water emulsion solvent evaporation-extraction method. The morphology of the MS was evaluated by scanning electron microscopy (SEM). The release characteristic of the TGF-β3 MS was evaluated. A New Zealand rabbit model for experimental osteoarthritis (OA) was established using the anterior medial meniscus excision method. Thirty OA rabbits were divided randomly into three groups according to different treatments of the right knee joints on day 7 after surgery: hADSCs/MS group received injection of both hADSCs and TGF-β3 MS; hADSCs group was injected with hADSCs; control group was injected with normal saline. Gross observation, histological staining and RT-PCR for collagen II and aggrecan) were used to assess the severity of OA and for evaluating the effect of combined use of hADSCs and TGF-β3 MS on articular cartilage regeneration in vivo. The MS were spherical with a smooth surface and the average diameter was 28 ± 2.3 µm. The encapsulation efficiency test showed that 73.8 ± 2.9% of TGF-β3 were encapsulated in the MS. The release of TGF- β3 lasted for at least 30 days. At both 6 and 12 weeks after injection, three groups exhibited different degrees of OA. Histological analysis showed that the hADSCs/MS group exhibited less OA than the hADSCs group, and the control group exhibited the most severe OA. Real-time RT-PCR showed that the gene expression of both collagen II and aggrecan were significantly up-regulated in the hADSCs/MS group. At 12 weeks after injection, the hADSCs/MS group also exhibited less OA than the other two groups. Combined use of hADSCs and TGF-β3 MS promoted articular cartilage regeneration in rabbit OA models.